Using motion analysis to enhance the performance of elite sprinters in Harare - Kamungeremu, Dicksson (BUSE, 2024)
This study assessed motion analysis to enhance the performance of elite sprinters in Harare. The research adopted a mixed method research design. From a population of 70 elite spinters and coaches , proportional stratified and random sampling method were employed to draw 56 questionnaire respondents for the study. Interviews were conducted on 7 coaches. Questionnaires were personally administered to the respondents at their workplaces.Interviews were also personally conducted by the researcher. Quantitative data were analysed with the help of the Statistical Package for Social Sciences (SPSS) version 21 whilst qualitative data was thematically analysed using NVivo. The study established that some motion analysis procedures were being utilized to enhance performance of elite sprinters in Harare as evidenced by average (M = 4.64 and ±SD= .749). It was however further found that motion analysis procedures are not being fully utilized in the training of elite sprinter to enhance performance given that some respondents were not aware of their use as shown by (M = 1.48 ±SD = .809). The study concluded that motion analysis contribute to greater performance of elite sprinters. It is recommended that motion analysis procedures be fully utilized in elite sprinter training to enhance their performance. After considering the limitations of study, areas for possible future research were also suggested.
Keywords: Motion Analysis; Elite sprinters